Hi‐LAB: A New Measure of Aptitude for High‐Level Language Proficiency. Issue 3 (4th June 2013) - Linck, Jared A.; Hughes, Meredith M.; Campbell, Susan G.; Silbert, Noah H.; Tare, Medha; Jackson, Scott R.; Smith, Benjamin K.; Bunting, Michael F.; Doughty, Catherine J.
<x xml:space="preserve">Abstract</x> Few adult second language (L2) learners successfully attain high‐level proficiency. Although decades of research on beginning to intermediate stages of L2 learning have identified a number of predictors of the rate of acquisition, little research has examined factors relevant to predicting very high levels of L2 proficiency. The current study, conducted in the United States, was designed to examine potential cognitive predictors of successful learning to advanced proficiency levels. Participants were adults with varying degrees of success in L2 learning, including a critical group with high proficiency as indicated by standardized language proficiency tests and on‐the‐job language use. Results from a series of group discrimination analyses indicate that high‐level attainment was related to working memory (including phonological short‐term memory and task set switching), associative learning, and implicit learning. We consider the implications for the construct of high‐level language aptitude and identify future directions for aptitude research.